Preparation process of nano chelated calcium, magnesium and zinc

By adopting the nano -chelating process in the calcium, magnesium, zinc zinc supplement, the use of ethyleine tetrazide and soy polypeptide collaborative chelars, and combined with high -pressure average method to prepare high -efficiency and high biological use of nano -chelated calcium magnesium magnesium magnesium magnesium magnesium magnesium magnesium magnesium Zinc solves the problem of low valid ion concentration and low biological utilization in existing technologies.

CN119344459AActive Publication Date: 2025-01-24SANYA BAITAI BIO-TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411884096.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-01-24
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The effective ion concentration in the chelates of existing calcium, magnesium, zinc supplements is low, and the bioavailability is not high, making it difficult to meet the needs of use.

Method used

The preparation process of nano-chelated calcium, magnesium zinc zinc, is used to play chelated effects through ethyleine tetrazide and soy polypeptides, combined with the anti-solve crystall crystal process and precipitation-high-voltage homogeneous method, prepare a nano-chew with a particle size of 130nm Combined magnesium zinc.

Benefits of technology

The chelating rate of calcium, magnesium zinc reached 97.3%, enhanced biological utilization, and solved the problem of low valid ion concentration and low biological utilization in existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119344459A_ABST
    Figure CN119344459A_ABST
Patent Text Reader

Abstract

The invention relates to the field of nutriment manufacturing, and discloses a preparation process of nano chelated calcium, magnesium and zinc. According to the preparation process, chelate and nanocrystalline technologies are combined, disodium ethylene diamine tetraacetate and soybean peptides are compounded, meanwhile, a precipitation-high-pressure homogenization process is combined, the chelation rate of the prepared nano chelated calcium, magnesium and zinc is as high as 97.3%, and the particle size D90 can reach 130 nm. Compared with the traditional calcium-magnesium-zinc supplements which are mostly inorganic mineral substances, have the general characteristics of water insolubility, poor in-vivo absorption and low bioavailability, the nano calcium-magnesium-zinc chelate prepared by the preparation method disclosed by the invention has the advantages that the bioavailability and solubility can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nutrient product manufacturing, and more specifically discloses a preparation process of nano-chelated calcium, magnesium and zinc. Background Art

[0002] Calcium, magnesium and zinc are essential nutrients for human growth and development. They also need to be supplemented in aquaculture and animal husbandry. Therefore, nutritional supplements of these elements have a large market capacity and good economic benefits.

[0003] The life activities of organisms such as neurotransmission, hormone release, osmotic pressure regulation, organ formation, growth and development, metabolism, etc. all rely on the participation of elements such as calcium, magnesium, and zinc. In the life activities of children and the elderly, these elements are often deficient due to various reasons and need to be supplemented in addition to food intake. During the special period of animal breeding, a large amount of required trace or macro elements are also needed to meet the needs of growth and development, thereby increasing the growth rate of animals and reducing diseases.

[0004] Artificially developed calcium, magnesium and zinc supplements are mainly divided into inorganic, organic and polypeptide chelate types. Most inorganic calcium, magnesium and zinc supplements are inorganic minerals, which are generally characterized by poor water solubility, poor absorption in the body and low bioavailability. Polypeptide chelate calcium preparations have the characteristics of good water solubility, high bioavailability and strong calcium absorption capacity. They are currently a hot spot for development. Their concentration is controllable and their release is stable. They are currently a popular research direction for solving the poor absorption of calcium supplements in the body. However, the chelation ability of simple metal ion chelators is greatly affected by pH value, the chelation rate is low, the chelate structure is unstable, etc., and it is generally difficult to meet the use requirements. How to improve the chelation ability of chelators and enhance the bioavailability of chelates is a technical problem that needs to be overcome. Summary of the invention

[0005] The invention mainly provides a preparation process of nanometer chelated calcium magnesium zinc to solve the problems of low effective ion concentration and low bioavailability in the chelate in the prior art.

[0006] To solve the above technical problems, according to one aspect of the present invention, more specifically, a preparation process of nano-chelated calcium, magnesium and zinc comprises the following steps:

[0007] S1. Weigh calcium chloride, magnesium chloride, zinc chloride, disodium ethylenediaminetetraacetate, and soybean polypeptide and add them into a dissolving kettle. Then add purified water into the dissolving kettle. After stirring to dissolve, heat to 30-60° C. and react for 1-3 hours to obtain reaction solution 1.

[0008] S2, filtering the reaction solution 1 prepared in step S1 through a precision filter into a crystallization kettle, and then dropping a monovalent saturated fatty alcohol into the crystallization kettle to precipitate white solid crystals;

[0009] S3, filtering the solid crystals obtained in step S2 through a centrifuge to obtain solid 1, washing solid 1 with 50% ethanol aqueous solution for 3-5 times, and drying to obtain solid 2;

[0010] S4, adding the solid 2 prepared in step S3 back into the crystallization kettle, adding deionized water, stirring and dissolving, adding monobasic saturated fatty alcohol dropwise, stirring to precipitate white solid crystals, and then adding poloxamer 188 into the clean kettle to obtain suspension 1;

[0011] S5, circulating the suspension 1 prepared in step S4 through a high-pressure homogenizer for 2-4 times to obtain a suspension 2;

[0012] S6. The suspension 2 prepared in step S5 is spray-dried to obtain nano-chelated calcium magnesium zinc.

[0013] Furthermore, in step S1, the weight ratio of calcium chloride, magnesium chloride, zinc chloride, disodium ethylenediaminetetraacetic acid, soybean polypeptide and purified water is 149:9:4:447:298:1500-4000.

[0014] Furthermore, in step S2, the weight ratio of the monohydric saturated fatty alcohol to the reaction solution 1 is 1-3:1.

[0015] Furthermore, in step S2, the pore size of the precision filter is 0.22-1 μm.

[0016] Furthermore, in step S2, the monohydric saturated alcohol is selected from one of methanol, ethanol and isopropanol.

[0017] Furthermore, in step S3, the drying method is one of forced air drying and vacuum drying, and the drying temperature is 50-60°C.

[0018] Furthermore, in step S4, the weight ratio of poloxamer 188, solid 2, deionized water, and monohydric saturated fatty alcohol is 0.01:1:10-20:10-40.

[0019] Furthermore, in step S5, the homogenization pressure of the high-pressure homogenizer is 40-90 MPa.

[0020] The preparation technology scheme provided by the present invention can chelate three nutritional elements of calcium, magnesium and zinc at the same time, and the chelation effect is synergistically exerted by disodium ethylenediaminetetraacetic acid and soybean polypeptide, and then the residual chloride ions in the system are removed by an anti-solvent crystallization process, and further combined with a precipitation-high-pressure homogenization method to prepare nano-sized chelated calcium, magnesium and zinc, with a chelation rate of up to 97.3% and a particle size of 130nm. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The present invention is further described in detail below with reference to the accompanying drawings and specific implementation methods.

[0022] Figure 1 Schematic diagram of the preparation process.

[0023] Figure 2 This is the particle size distribution spectrum of the chelated calcium magnesium zinc prepared in Example 3. DETAILED DESCRIPTION

[0024] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.

[0025] Example 1

[0026] Weigh 14.9 kg of calcium chloride, 9.0 kg of magnesium chloride, 4.0 kg of zinc chloride, 44.7 kg of disodium ethylenediaminetetraacetate, and 29.8 kg of soybean polypeptide, add them into a dissolution kettle, add 200 kg of purified water, stir and dissolve, heat to 40°C, and stir to react for 2 hours; filter the above reaction solution through a 0.45 μm precision filter into a crystallization kettle, add 320 kg of ethanol dropwise, and the addition is completed in about 4 hours to precipitate a white solid; filter with a centrifuge, wash the filter cake with 50% ethanol aqueous solution 5 times, and detect the filtrate with a silver nitrate solution until there is no turbidity , the washed filter cake was vacuum dried at 50°C to constant weight; the dried solid was added back into the crystallization kettle, 900kg of deionized water was added, and after stirring to dissolve, 900kg of ethanol was added dropwise, and white solid crystals were precipitated under stirring, and then 0.8kg of poloxamer 188 was added to the clean kettle, and stirred for 30 minutes to obtain a suspended reaction liquid; the prepared suspended reaction liquid was circulated and homogenized in a homogenizer for 2 times, the pressure was controlled at 40MPa, and then homogenized once at 70MPa; the homogenized liquid was spray-dried to obtain a nano-chelated calcium magnesium zinc product.

[0027] Example 2

[0028] Weigh 14.9 kg of calcium chloride, 9.0 kg of magnesium chloride, 4.0 kg of zinc chloride, 44.7 kg of disodium ethylenediaminetetraacetate, and 29.8 kg of soybean polypeptide, add them into a dissolving kettle, add 400 kg of purified water, stir and dissolve, heat to 40°C, and stir to react for 2 hours; filter the above reaction solution through a 1 μm precision filter into a crystallization kettle, add 1004 kg of methanol dropwise, and add dropwise for about 6 hours to precipitate a white solid; filter with a centrifuge, wash the filter cake with 50% ethanol aqueous solution 5 times, and detect the filtrate with a silver nitrate solution until there is no turbidity. The washed filter cake was dried at 60°C under forced air drying until constant weight; the dried solid was added back into the crystallization kettle, 900 kg of deionized water was added, and after stirring for dissolution, 900 kg of methanol was added dropwise, and white solid crystals were precipitated under stirring; then 0.8 kg of poloxamer 188 was added into the clean kettle, and stirred for 30 min to obtain a suspension reaction liquid; the prepared suspension reaction liquid was circulated and homogenized in a homogenizer for 2 times, the pressure was controlled at 40 MPa, and then homogenized once at 80 MPa; the homogenized liquid was spray dried to obtain a nano-chelated calcium magnesium zinc product.

[0029] Example 3

[0030] Weigh 14.9 kg of calcium chloride, 9.0 kg of magnesium chloride, 4.0 kg of zinc chloride, 44.7 kg of disodium ethylenediaminetetraacetate, and 29.8 kg of soybean polypeptide, add them into a dissolving kettle, add 200 kg of purified water, stir and dissolve, heat to 40°C, and stir to react for 2 hours; filter the above reaction solution through a 0.22 μm precision filter into a crystallization kettle, add 320 kg of ethanol dropwise, and add dropwise for about 4 hours to precipitate a white solid; filter with a centrifuge, wash the filter cake with 50% ethanol aqueous solution 5 times, and detect the filtrate with silver nitrate solution until there is no turbidity. The cake was vacuum dried at 60°C to constant weight; the dried solid was added back into the crystallization kettle, 900 kg of deionized water was added, and after stirring to dissolve, 900 kg of ethanol was added dropwise, and white solid crystals were precipitated under stirring, and then 0.8 kg of poloxamer 188 was added to the clean kettle, and stirred for 30 minutes to obtain a suspension reaction liquid; the suspension reaction liquid prepared above was circulated and homogenized in a homogenizer for 2 times, the pressure was controlled at 40 MPa, and then homogenized once at 90 MPa; the homogenized liquid was spray dried to obtain a nano-chelated calcium magnesium zinc product, and the particle size analysis test spectrum is shown in the attached Figure 2 .

[0031] Example 4

[0032] Weigh 14.9 kg of calcium chloride, 9.0 kg of magnesium chloride, 4.0 kg of zinc chloride, 44.7 kg of disodium ethylenediaminetetraacetate, and 29.8 kg of soybean polypeptide, add them into a dissolving kettle, add 200 kg of purified water, stir and dissolve, heat to 40°C, and stir to react for 2 hours; filter the above reaction solution through a 0.45 μm precision filter into a crystallization kettle, add 320 kg of ethanol dropwise, and add dropwise for about 4 hours to precipitate a white solid; filter with a centrifuge, wash the filter cake with 50% ethanol aqueous solution 5 times, and detect the filtrate with a silver nitrate solution until there is no turbidity. The washed filter cake was vacuum dried at 50°C to constant weight; the dried solid was added back into the crystallization kettle, 900 kg of deionized water was added, and after stirring for dissolution, 900 kg of isopropanol was added dropwise, and white solid crystals were precipitated under stirring, and then 0.8 kg of poloxamer 188 was added to the clean kettle, and stirred for 30 minutes to obtain a suspended reaction liquid; the prepared suspended reaction liquid was circulated and homogenized in a homogenizer once, the pressure was controlled at 40 MPa, and then homogenized once at 70 MPa; the homogenized liquid was spray dried to obtain a nano-chelated calcium magnesium zinc product.

[0033] Example 5

[0034] Weigh 14.9 kg of calcium chloride, 9.0 kg of magnesium chloride, 4.0 kg of zinc chloride, 44.7 kg of disodium ethylenediaminetetraacetate, and 29.8 kg of soybean polypeptide, add them into a dissolution kettle, add 200 kg of purified water, stir and dissolve, heat to 40°C, and stir to react for 2 hours; filter the above reaction solution through a 0.45 μm precision filter into a crystallization kettle, add 320 kg of isopropanol dropwise, and the addition is completed in about 4 hours to precipitate a white solid; filter with a centrifuge, wash the filter cake with 50% ethanol aqueous solution 5 times, and detect the filtrate with a silver nitrate solution until there is no turbidity , the washed filter cake was vacuum dried at 50°C to constant weight; the dried solid was added back into the crystallization kettle, 900kg of deionized water was added, and after stirring to dissolve, 900kg of isopropanol was added dropwise, and white solid crystals were precipitated under stirring, and then 0.8kg of poloxamer 188 was added to the clean kettle, and stirred for 30 minutes to obtain a suspended reaction liquid; the prepared suspended reaction liquid was circulated and homogenized in a homogenizer for 2 times, the pressure was controlled at 40MPa, and then homogenized for 2 times at 70MPa; the homogenized liquid was spray-dried to obtain a nano-chelated calcium magnesium zinc product.

[0035] The test conditions and results of Examples 1-5 are shown in Table 1 below:

[0036] Table 1: Experimental conditions and results of the examples

[0037] sample High pressure homogenization pressure (MPa) Number of homogenization cycles (times) Calcium, magnesium and zinc chelation rate (%) Particle size D90 (nm) Example 1 70 3 96.8 166 Example 2 80 3 97.1 147 Example 3 90 3 97.3 130 Example 4 70 2 95.7 220 Example 5 70 4 96.4 140

[0038] Test results: The homogenization times of Examples 1, 2, and 3 are the same. As the homogenization pressure increases, the product particle size becomes smaller; the homogenization pressure of Examples 1, 4, and 5 is the same. As the number of homogenization cycles increases, the product particle size becomes smaller; the calcium, magnesium, and zinc chelation rates are consistent, and can reach up to 97.3%.

[0039] Experimental conclusion: The preparation process conditions of this scheme can obtain a higher calcium magnesium zinc chelation rate, and the product particle size is small, reaching the nanometer level; the homogenization pressure and number of times have a significant effect on the particle size.

[0040] Comparative Example 1

[0041] Weigh 14.9 kg of calcium chloride, 9.0 kg of magnesium chloride, 4.0 kg of zinc chloride, and 74.5 kg of disodium ethylenediaminetetraacetate, add them into a dissolving kettle, add 150 kg of purified water, stir and dissolve, heat to 40°C, and stir to react for 2 hours; filter the above reaction solution through a 1 μm precision filter into a crystallization kettle, add 450 kg of methanol dropwise, and add it for about 6 hours to complete the addition, and a white solid is precipitated; filter with a centrifuge, wash the filter cake with 50% ethanol aqueous solution 5 times, and detect the filtrate with silver nitrate solution until there is no turbidity. The mixture was dried at 60°C by forced air drying until constant weight; the dried solid was added back into the crystallization kettle, 900 kg of deionized water was added, and after stirring for dissolution, 900 kg of methanol was added dropwise, and white solid crystals were precipitated under stirring; 0.8 kg of poloxamer 188 was added into the clean kettle, and the mixture was stirred for 30 min to obtain a suspension reaction liquid; the suspension reaction liquid prepared above was circulated and homogenized in a homogenizer for 2 times, the pressure was controlled at 40 MPa, and then homogenized once at 90 MPa; the homogenized liquid was spray dried to obtain a nano-chelated calcium magnesium zinc product.

[0042] Comparative Example 2

[0043] Weigh 14.9 kg of calcium chloride, 9.0 kg of magnesium chloride, 4.0 kg of zinc chloride, and 74.5 kg of soybean polypeptide, add them into a dissolving kettle, add 150 kg of purified water, stir and dissolve, heat to 40°C, and stir to react for 2 hours; filter the above reaction solution through a 1 μm precision filter into a crystallization kettle, add 450 kg of methanol dropwise, and add it for about 6 hours to precipitate a white solid; filter with a centrifuge, wash the filter cake with 50% ethanol aqueous solution for 5 times, and detect the filtrate with silver nitrate solution until there is no turbidity. ℃ and dried by forced air to constant weight; the dried solid was added back into the crystallization kettle, 900 kg of deionized water was added, and after stirring for dissolution, 900 kg of methanol was added dropwise, and white solid crystals were precipitated under stirring; then 0.8 kg of poloxamer 188 was added into the clean kettle, and stirred for 30 min to obtain a suspension reaction liquid; the suspension reaction liquid prepared above was circulated and homogenized in a homogenizer for 2 times, the pressure was controlled at 40 MPa, and then homogenized once at 80 MPa; the homogenized liquid was spray dried to obtain a nano-chelated calcium magnesium zinc product.

[0044] The comparative example investigated the effect of chelating agents on the chelation rate of calcium, magnesium and zinc, which is summarized in Table 2 below:

[0045] Table 2: Summary of the effects of chelating agent dosage

[0046] sample Disodium EDTA Soybean Peptide Calcium, magnesium and zinc chelation rate (%) Example 2 3 2 97.1 Comparative Example 1 5 0 72.4 Comparative Example 2 0 5 59.6

[0047] Note: The chelating agent dosage in the table is the weight ratio of the chelating agent to calcium chloride.

[0048] Test results: The chelation rate of calcium, magnesium and zinc in Example 2 is significantly better than that in Comparative Examples 1 and 2;

[0049] Experimental conclusion: Disodium EDTA and soybean peptide can play a synergistic role. A single chelating agent may not be able to have a high chelating ability for calcium, magnesium and zinc ions at the same time.

[0050] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention also fall within the protection scope of the present invention.

Claims

1. A preparation process of nano-chelated calcium magnesium zinc, characterized in that: The following steps are involved: S1. Weigh calcium chloride, magnesium chloride, zinc chloride, disodium ethylenediaminetetraacetate, and soybean polypeptide and add them into a dissolving kettle. Then add purified water into the dissolving kettle. After stirring to dissolve, heat to 30-60° C. and react for 1-3 hours to obtain reaction solution 1. S2, filtering the reaction solution 1 prepared in step S1 through a precision filter into a crystallization kettle, and then dropping a monovalent saturated fatty alcohol into the crystallization kettle to precipitate white solid crystals; S3, filtering the solid crystals obtained in step S2 through a centrifuge to obtain solid 1, washing solid 1 with 50% ethanol aqueous solution for 3-5 times, and drying to obtain solid 2; S4, adding the solid 2 prepared in step S3 back into the crystallization kettle, adding deionized water, stirring and dissolving, adding monobasic saturated fatty alcohol dropwise, stirring to precipitate white solid crystals, and then adding poloxamer 188 into the clean kettle to obtain suspension 1; S5, circulating the suspension 1 prepared in step S4 through a high-pressure homogenizer for 2-4 times to obtain a suspension 2; S6. The suspension 2 prepared in step S5 is spray-dried to obtain nano-chelated calcium magnesium zinc.

2. The preparation process of nano-chelated calcium magnesium zinc according to claim 1, characterized in that: In step S1, the weight ratio of calcium chloride, magnesium chloride, zinc chloride, disodium ethylenediaminetetraacetic acid, soybean polypeptide and purified water is 149:9:4:447:298:1500-4000.

3. The preparation process of nano-chelated calcium magnesium zinc according to claim 1, characterized in that: In step S2, the weight ratio of the monohydric saturated fatty alcohol to the reaction solution 1 is 1-3:

1.

4. The preparation process of nano-chelated calcium magnesium zinc according to claim 1, characterized in that: In step S2, the pore size of the precision filter is 0.22-1 μm.

5. The preparation process of nano-chelated calcium magnesium zinc according to claim 1, characterized in that: In step S2, the monohydric saturated alcohol is selected from one of methanol, ethanol and isopropanol.

6. The preparation process of nano-chelated calcium magnesium zinc according to claim 1, characterized in that: In step S3, the drying method is one of forced air drying and vacuum drying, and the drying temperature is 50-60°C.

7. The preparation process of nano-chelated calcium magnesium zinc according to claim 1, characterized in that: In step S4, the weight ratio of poloxamer 188, solid 2, deionized water, and monohydric saturated fatty alcohol is 0.01:1:10-20:10-40.

8. The preparation process of nano-chelated calcium magnesium zinc according to claim 1, characterized in that: In step S5, the homogenization pressure of the high-pressure homogenizer is 40-90 MPa.

Citation Information

Patent Citations

  • Amoitone B nano crystallization preparation and preparation method thereof

    CN102579373A

  • Sugar alcohol calcium magnesium zinc boron compound liquid fertilizer and preparation method and applications thereof

    CN103588564A

  • Manufacture method of sacha inchi polypeptide

    CN105767452A

  • Preparation method of soybean polypeptide chelated calcium

    CN106387920A

  • Metal ion complexes

    CN108026114A